Penguatan Identitas Gender pada Siswa Laki-laki Melalui Kehadiran Guru Laki-laki di Tingkat PAUD - Al Baqi, Safiruddin (Martabat: Jurnal Perempuan dan Anak, 2021)
Abstract: Gender identity typically aware at the age of two and will strengthen until about five years old. It is important for parents and teacher of early childhood education to provide knowledge and strengthen children's gender identity so that their gender identity develops according to their gender. Teachers in schools play an important role in strengthening gender identity. Unfortunately, today's society is not much aware of the importance of it and teachers of early childhood education are still considered as women's professions. This article aims to explain the importance of the presence of male teachers on the strengthen of gender identity in early childhood students. This study used a literature review method with thematic analysis techniques. The results of the research analysis showed that society still gives a stigma that early childhood teachers must be women because they have more patience and so on. It creates a sense of prestige and shame for men to become early childhood teachers. On the other hand, male teachers are very much needed at the early childhood education level because male teachers have a role that cannot be replaced by female teachers, especially in the formation and strengthening of gender identity for male students, including providing challenging games for male students, giving examples of assertive behavior, and other attributes that show male gender roles in front of male students. Keywords: Early childhood education, gender identity, male student, male teacher. Abstrak: Identitas gender mulai terbentuk pada usia dua tahun dan akan menguat sampai sekitar usia lima tahun. Penting bagi orang tua dan guru Pendidikan Anak Usia Dini (PAUD) untuk memberikan pengetahuan dan penguatan tentang identitas gender anak agar identititas gendernya berkembang sesuai dengan jenis kelamin yang dimiliki. Guru di sekolah memberikan pengaruh penting bagi penguatan identitas gender. Namun sayangnya masyarakat saat ini belum banyak yang menyadari pentingnya hal itu dan guru PAUD masih di anggap sebagai profesi perempuan. Artikel ini bertujuan untuk memaparkan pentingnya keberadaan guru laki-laki terhadap pembentukan identitas gender pada siswa PAUD. Penelitian ini menggunakan metode literature review atau studi pustaka dengan teknik analisis tematik. Hasil analisis penelitian menunjukkan bahwa masyarakat masih memberikan stigma bahwa guru PAUD haruslah perempuan karena memiliki kesabaran lebih dan lain-lain. Hal ini memunculkan rasa gengsi dan malu bagi laki-laki untuk menjadi guru PAUD. Di sisi lain, guru laki-laki sangatlah diperlukan di tingkat pendidikan anak usia dini karena guru laki-laki memiliki peran yang tidak bisa digantikan oleh guru perempuan khususnya dalam pembentukan dan penguatan identitas gender bagi siswa laki-laki, diantaranya pemberian permainan yang menantang bagi anak laki-laki, pemberian contoh perilaku tegas, serta atribut lain yang menunjukkan peran gender laki-laki dihadapan siswa laki-laki. Kata kunci: Identitas gender, guru laki-laki, PAUD, siswa laki-laki.